Extracellular Release and Signaling by Heat Shock Protein 27: Role in Modifying Vascular Inflammation - Batulan, Zarah; Pulakazhi Venu, Vivek Krishna; Li, Yumei; Koumbadinga, Geremy; Alvarez-Olmedo, Daiana Gisela; Shi, Chunhua; O’Brien, Edward R. (Frontiers in Immunology, 2016)
Heat shock protein 27 (HSP27) is traditionally viewed as an intra-cellular chaperone protein with anti-apoptotic properties. However, recent data indicate that a number of heat shock proteins, including HSP27, are also found in the extra-cellular space where they may signal via membrane receptors to alter gene transcription and cellular function. Therefore, there is increasing interest in better understanding how HSP27 is released from cells, its levels and composition in the extracellular space and the cognate cell membrane receptors involved in effecting cell signaling. In this paper the knowledge to date, as well as some emerging paradigms about the extracellular function of HSP27 are presented. Of particular interest is the role of HSP27 in attenuating atherogenesis by modifying lipid uptake and inflammation in the plaque. Moreover, the abundance of HSP27 in serum is an emerging new biomarker for ischemic events. Finally, HSP27 replacement therapy may represent a novel therapeutic opportunity for chronic inflammatory disorders such as atherosclerosis.